Relasi Pemahaman Ekologis dengan Perilaku Ekologis Mahasiswa Perguruan Tinggi Katolik di Indonesia - Roida Sihombing; Bonifasius Bonifasius; Maria Magdalena; Yly Suardy; Gregorius Redwan; Sebastianus Aldo; Alfeus Sunarso (STIKAS Santo Yohanes Salib Kalimantan Barat, 2026)
TThis study aims to analyze the relationship between ecological understanding and ecological behavior among students at Catholic higher education institutions in Indonesia, as well as to gain a deeper understanding of the factors influencing their ecological behavior. The study employed a mixed methods approach using a sequential explanatory design, in which quantitative data were collected and analyzed first, followed by qualitative data collection and analysis to strengthen and explain the quantitative findings. The quantitative phase involved 109 respondents selected through purposive sampling, while the qualitative phase involved 12 participants selected based on the diversity of their responses and their willingness to provide more in-depth information. Data were collected using a 20-item closed-ended Likert-scale questionnaire and an open-ended questionnaire. Quantitative data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression, whereas qualitative data were analyzed through thematic analysis. The findings indicate that students’ ecological understanding and ecological behavior were both at a high level. Pearson correlation analysis revealed a significant positive relationship between ecological understanding and ecological behavior (r = 0.615; p < 0.001). Regression analysis showed that ecological understanding accounted for 37.9% of the variance in ecological behavior, while the remaining 62.1% was explained by other factors. The qualitative findings revealed that students’ ecological behavior was influenced by personal habits, social environment, the availability of campus facilities, and an environmentally supportive campus culture. These findings suggest that improving ecological understanding should be accompanied by institutional policies and the development of an ecological culture to encourage the consistent implementation of ecological behavior in everyday life.